Comparative study between blocked intramedular rod and DHS / DCS / DCP plates in the treatment of fractures in the lower member at the University Hospital Presidente Dutra (Research, Society and Development, 2022)
Introduction: With the increase in the incidence of fractures resulting from high-impact accidents, the locked nail system started to be used, becoming the method of choice in countries where the material is available. Objective: To compare total hospitalization, need to stay in the intensive care unit, use of blood concentrate, drainage tubes, postoperative infection, rehabilitation and quality of life in patients with lower limb fracture fixation methods. President Dutra University. Methods: A review of the current literature on the subject was carried out, data were collected through the review of 40 charts, divided into groups A and B: group A (intramedullary nail obstruction) and group B (DHS, DCS and DCP plates ), considering variables: Total length of stay, length of stay in the intensive care unit, use of blood concentrates, drains, postoperative infection, recovery and pain assessment. Final considerations: The effectiveness of the use of intramedullary nail was evidenced in terms of early rehabilitation of the patient, shorter hospital stay, lower rate of postoperative infection, shorter ICU stay, less use of packed red blood cells, without the need for the use of drain and, consequently, lower hospital costs and improved quality of life for the patient.